Tryptanthrin from indigo: Synthesis, excited state deactivation routes and efficient singlet oxygen sensitization - Pinheiro, Daniela (2020)
The microwave-assisted synthesis of tryptanthrin from indigo in mild oxidation conditions, and a comprehensive study of the excited state properties of this compound in a variety of solvents with different polarity and viscosity values at room and low temperatures are reported. In contrast with indigo, emission of the triplet state of tryptanthrin is observed with a very efficient singlet oxygen sensitization quantum yield, indicating that the triplet state is efficiently populated. From time-resolved fluorescence and femtosecond transient absorption data, further supported with time-dependent density functional theory (TDDFT) calculations, two species, with S1 states with locally excited (LE) of π,π* nature and a charge transfer (CT) of n,π* characteristics, originated from an initially populated Frank-Condon S2 state (π,π*), are observed. The two electronically independent species are energetically nearly degenerate and inter-conversion is predicted (and rate constants determined) to occur between LE (S1) and CT (S1) species. Due to the low value of the fluorescence quantum yield (~10−3) and high triplet state yield (ϕT≥ϕΔ), the high stability of this compound is associated to the high efficiency of the radiationless deactivation processes which involve the formation of the CT state which efficiently converts, through S1 ~~> Tn intersystem crossing, to the T1 triplet state.